A giant neurofibroma of the chest wall and neck – a case report - Gałęcki, Bartłomiej; Piwkowski, Cezary; Kasprzyk, Mariusz; Gabryel, Piotr; Dyszkiewicz, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
A case of giant neck and chest tumor (neurofibroma) in a disabled patient, that disrupted his daily life activity was presented. The tumor was completely removed with a margin of healthy tissue. The postoperative course was complicated by systemic inflammatory response syndrome (SIRS). The patient was discharged from the hospital 16 days after surgery. Eleven months later there was no evidence of general and local recurrence of the tumor.